Temperature‐ and Humidity‐Dependent Phase States of Secondary Organic Aerosols. Issue 2 (16th January 2019) - Petters, Sarah S.; Kreidenweis, Sonia M.; Grieshop, Andrew P.; Ziemann, Paul J.; Petters, Markus D.
Abstract: Viscosity of monoterpene‐derived secondary organic aerosols (SOAs) as a function of temperature and relative humidity (RH), and dry SOA glass transition temperatures are reported. Viscosity was measured using coalescence time scales of synthesized 100 nm dimers. Dry temperature‐dependent SOA viscosity was similar to that of citric acid, coal tar pitch, and sorbitol. The temperature where dry viscosity was 10 6 Pa·s varied between 14 and 36 °C and extrapolated glass transition varied between −10 and 20 °C (±10 °C). Mass fragment f 44 obtained with an Aerosol Chemical Speciation Monitor was anticorrelated with viscosity. Viscosity of humidified Δ 3 ‐carene and α‐pinene SOAs exceeded 10 6 Pa·s for all subsaturated RHs at temperatures <0 and –5 °C, respectively. Steep viscosity isopleths at 10 6 Pa·s were traced for these across (temperature, RH) conditions ranging from (approximately −5 °C, 100%) and (approximately 36 °C, 0%). Differences in composition and thus hygroscopicity can shift humidified viscosity isopleths for SOAs at cold tropospheric temperatures. Plain Language Summary: Airborne particles in the environment can be harmful to human health and are part of the climate system. These particles and any harmful substances they may carry can be broken down by oxidants or removed by water. This is easier if the particles are liquid and becomes more difficult if particles are semisolid (like peanut butter) or solid (like glass). However, viscosity is hard to measure for nanoscale airborne particles. Recent advances have made this possible. In this study we measured the viscosity of several types of oxidized organic aerosols at different temperatures and humidities. We collided and melted together 100 nm particles in a continuous flow system. Without moisture, the particles were as hard as pitch and melted between 14 and 36 °C. At temperatures 20° colder they could be considered as hard as glass. The chemical marker for more oxidized material was correlated with softer particles. Below −5° we were unable to liquefy the particles even with high relative humidity. The particles melted at about −5° at 100% relative humidity and at 36° dry, with intermediate points connecting these extremes. We found that the composition and water solubility of the particles affects their viscosity at cold temperatures. Key Points: Differences in composition and hygroscopicity shift humidified viscosity isopleths for secondary organic aerosols at cold temperatures Temperature dependence of viscosity for dry secondary organic aerosol was similar to that of citric acid, coal tar pitch, and sorbitol For monoterpene‐derived secondary organic aerosols, the temperature where viscosity was 10 6 Pa·s was anticorrelated with oxidation state